Fabrication and Evaluation of an Affordable Infant Radiant Warmer for use in Limited Resource Settings - Ibitoye, M. O.; Ahmed, Y. K.; Saad, A. B.; Ajibola, T. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
The challenges of thermoregulation due to hypothermia, which is believed to underlie high infant morbidity and mortality rate, is common with underweight or preterm infants especially those from limited resource settings. Available devices in the market to check hypothermia are expensive, especially for most countries with between 2% to 10% of GDP on the healthcare budget. Affordable thermoregulation realization for infants is therefore of significant clinical importance in these settings. The aim of this study was to design and fabricate an affordable (110) and clinically useful radiant warmer to facilitate hypothermia treatment. The radiant warmer was fabricated with an overhead radiant heater for heat radiation targeted at infants laid in a clinically comfortable foam mattress in a bassinet. A portable fan was placed above the heating element to facilitate downward heat flow. A biocompatible temperature sensor was also placed on the bassinet to monitor the infant’s body temperature. The warmer incorporated an Arduino-based PID temperature microcontroller to regulate the temperature of the heating element. The warmer, with castor wheels to aid the device’s mobility, has a strong and durable galvanized pipe stand capable of supporting the device. The device performance indicated an acceptable physiological heating temperature range of 36 °C - 36.5 °C within 20 min of warm-up and up to 36.7 °C in 30 min of use. Therefore, the device can be adjudged potentially useful in facilitating thermoregulation in infants by providing suitable thermal support. With these results and the potential of the device to reduce infant mortality rates and promote their growth, it is hereby recommended that the device may be fully deployed for clinical application.